Biodiversity in PT Pertamina Patra Niaga Fuel Terminal Sei Siak Mor 1 Sumbagut - Syofiyardi Syofiyardi; Riyadiyanto Riyadiyanto; Siti Maisarah (International Journal of Social Service and Research, 2022)
The areas of Tanjung Rhu and Limbungan villages are areas that are bordered by the Siak river. The existence of the Siak River in the Pekanbaru community is one of the connecting routes with other areas, as well as the entry of goods from within and outside the Pekanbaru area. Where there is the main port of the Daku River which is still used for its function today as transportation access. This transportation access has an impact on river abrasion. This study aims to acknowledge biodiversity condition in PT Pertamina. This study uses descriptive qualitative methods with data collection techniques, documentation studies, and in-depth interviews. The results of the study show that the condition of the Siak River in recent times has not received special attention from the government. PT Pertamina Patra Niaga Fuel Terminal Sei Siak highlights environmental aspects and the sustainability of biodiversity around the company's operations in order to be maintained and sustainable by initiating an Ecotourism program by planting mangrove seedlings, planting several types of trees and plants to reduce carbon dioxide and maintaining aquatic biota ecosystems. as well as the mainland. There are also animal conservation activities, namely the Serindit Bird to maintain endemic animal ecosystems in the Semut Island Ecotourism Area.